The Negotiation of Religious Identity through Reincarnation and Ritual Healing: A Study of the Dayak Tunjung Christian Community, Indonesia - Panggarra, Robi; Luthy, Christopher James; Tombuku, Praity Brenda (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2024)
This study explores how members of the Dayak Tunjung Christian community in Lamin Telihan, East Kalimantan, continue to practise and affirm traditional beliefs in reincarnation (Suli) and ritual healing (Belian) despite their formal affiliation with the Evangelical Christian Church (GKII). The research aims to understand the dynamics of religious identity negotiation between institutional Christianity and local cosmological frameworks that have long shaped the community’s worldview. Using a qualitative approach and grounded theory methodology, data were collected through semi-structured interviews, observations, and field notes involving traditional leaders, church members, and community elders. The findings reveal that Suli and Belian persist not merely as residual pre-Christian practices but as active, meaningful expressions of lived religion that contribute to spiritual resilience and cultural continuity. These practices function as alternative frameworks for interpreting life, death, and healing—often offering more inclusive and contextually relevant narratives than doctrinal Christian eschatology. The study shows that religious conversion among the Dayak Tunjung is not a linear or total rupture from the past but a layered process of hybridisation and negotiation. The research contributes to scholarship on syncretism, vernacular religion, and ethical pluralism by presenting a unique Indonesian case where indigenous cosmologies coexist with global religious structures. This originality lies in its focus on reincarnation within a Christian setting—a subject rarely explored in Southeast Asian contexts—highlighting the adaptive and dialogical nature of religiosity in multicultural societies.